viernes, 4 de febrero de 2011

· Y=3x (5x+2)







Y= (5+2x)3+3x (2)
Y=15+6x+6x
Y=15+12x


(x2+1)(3x-6)
Y= (3x-6)2x+ ( +1)3
Y=6 -12x+3 +3
Y=9 -12x+3

Y= (3x+7) x3

Y= ( 3+ (3x+7)3
Y= 3 +9 +21
Y=12 +21
·

Y=(2x-1)(3x-7)

Y= (3x-97)2+ (2x-1)3
Y=6x-14+6x-3
Y=12x-17
·

Y=(x+1)(x-1)


Y=(x-1)1+(x+1)1
Y=x-1+x+1
Y=
·


Y=2x4 (x4 -3)

Y= ( -3)8 + (2 )4
Y=8 -24 +8
Y=16 -24
·

Y= (3x+7) x7

Y= ( x7)3+ (3x+7)7 x6
Y=3 +21 -49
Y=24 -49 Y= ( +1) (- +3)

y=(x2+1)(x2+3)

Y= (- +3)2x+ ( +1)-2x
Y=-2 -6x-2 +2x
Y=-4 -4x

No hay comentarios:

Publicar un comentario